Development of Wattpad-Based Learning Media on Materials Avoiding Promiscuity in Secondary Schools - Putriani, Putriani; Riawarda, A.; Makmur, Makmur; Arisal, Andi (Educational Journal of Learning Technology, 2024)
This research aims to develop and evaluate the effectiveness of Wattpad-based learning media on the material "Staying Away from Promiscuity" at SMA Negeri 5 Luwu. This media is designed to increase students' interest and understanding in Islamic Religious Education. The research method follows the ADDIE model, which includes analysis, design, development, implementation, and evaluation. Media is designed by creating covers, characters, and materials, then validated by media, materials, language, and learning experts. The implementation involved trials on 29 students and evaluations using pre-tests and post-tests. The study results showed that the media was declared very valid by all validators and received a positive response from students, with aspects of media, attractiveness, material, and language obtaining an average score of "Very Valid". The increase in the average score from pre-test (49) to post-test (90) and the percentage of post-test scores (80%) indicate the effectiveness of the media in increasing students' understanding and motivation. This study recommends expanding the use of technology in learning and training for teachers.